NUMERICAL STUDY OF DIFFERENT ORRIFICES SHAPES EFFECT ON THE HYDRODYNAMICS OF BUBBLING FLUIDIZED BED - IBRAHIM, MUHAMAD HILMEE (2013)
Fluidized bed has been used in wide applications due to its capability to provide a good mixing medium and heat transfer. It has been used and utilized for many processes in industrial scale on various applications such as catalytic cracking in the petroleum industry and gasification process in the energy industry. The main focus ofthis work is to investigate a parameter for the fluidized bed operating in a bubbling regimes; the effect of different orifice shape on fluidization uniformity. For this purpose, Three (3) different orifice shapes were used, a classic straight drilled hole perforated plate (cylindrical), a nozzle like shape (nozzle), and also a diffuser like shape (diffuser).